PERAN AKUNTABILITAS DAN TRANSPARANSI PEMERINTAH DESA INDONESIA TERHADAP KEPERCAYAAN MASYARAKAT DESA: KASUS DI KABUPATEN BANTUL - Hafiez Sofyani; Afrizal Tahar (Universitas Muhammadiyah Malang, 2021)
This study aims to examine effect of accountability and transparency of village government on village community trust. A Mixed-methods research design with explanatory sequential model was adopted in this study. Data were collected by distributing a survey questionnaire in the first step and followed by interviews. Partial Least Square (PLS) technique was used to test the hypotheses whilst inductive thematic analysis was adopted to analyze interview data. This study discovered that the transparency enhances village community trust while accountability was in contrast. The interview results complement the result obtained from hypotheses testing using survey data. Based on the research findings, the transparency becomes a critical factor for increasing community trust in village.